On uniform observability of gradient flows in the vanishing viscosity limit - Laurent, Camille; Léautaud, Matthieu (Journal de l'École polytechnique. Mathématiques, 2021)
We consider a transport equation by a gradient vector field with a small viscous perturbation −ε∆_g. We study uniform observability (resp. controllability) properties in the (singular) vanishing viscosity limit ε → 0 + , that is, the possibility of having a uniformly bounded observation constant (resp. control cost). We prove with a series of examples that in general, the minimal time for uniform observability may be much larger than the minimal time needed for the observability of the limit equation ε = 0. We also prove that the two minimal times coincides for positive solutions. The proofs rely on a semiclassical reformulation of the problem together with (a) Agmon estimates concerning decay of eigenfunctions in the classically forbidden region [HS84] (b) fine estimates of the kernel of the semiclassical heat equation [LY86]. On considère une équation de transport par un champ de vecteurs gradient avec une petite perturbation visqueuse −ε∆_g. Nous étudions l'observabilité uniforme (resp. contrôlabilité) dans la limite (singulière) de viscosité évanescente ε → 0 + , c'est à dire la possibilité d'obtenir une constante d'observation uniformément bornée (resp. un coût du contrôle). Nous prouvons par une série d'exemples, qu'en général, le temps minimal pour l'observation uniforme peut être bien plus grand que le temps minimal nécessaire pour l'observation de l'équation limite ε = 0. Nous prouvons aussi que les deux temps minimaux coïncident pour des solutions positives. Les preuves reposent sur une reformulation semi-classique du problème ainsi que (a) des estimées d'Agmon concernant la décroissance de fonctions propres dans la zone classiquement interdite [HS84] (b) des estimations fines du noyau de l'équation de la chaleur semi-classique [LY86].